PENERAPAN TERAPI KELOMPOK TERAPEUTIK KANAK-KANNAK DAN PSIKOEDUKASI KELUARGA PADA ANAK DAN ORANGTUA TERHADAP PERKEMBANGAN OTONOMI ANAK - Deasti Nurmaguphita; Budi Anna Keliat; Yossie Susanti Eka Putri (Jurnal Ilmu Keperawatan Jiwa, 2018)
APPLICATION OF TODDLER THERAPEUTIC GROUP THERAPY AND FAMILY PSYCHOEDUCATION IN TODDLER AND PARENTS TOWARD DEVELOPMENT OF TODDLER AUTONOMY.  ABSTRACTThe health promotion for children in society still focuses on the physical, while psychosocial stimulation in children still minimize. The purpose of the scientific writing was to report the result of Therapeutic Group Therapy and Family Pshychoeducation toddler autonomy and stimulation ability of parents in toddler stimulation. This case study used Health Promotion Theory and Adaptation Model Stuart. The number of children and parents who received Therapeutic Group Therapy were 20 persons, while 15 of them received Family Pshychoeducation. The result of Therapeutic Group therapy found increased autonomy children development and the ability of parents to stimulate their toddler. Furthermore 15 parents who received Family Pshychoeducation have increased their ability to stimulate their children, and their children autonomy were higher. It was recomended these therapys to be applied to the children and their parents as a part of Health Promotion. Keywords: Autonomy, toddler, Therapeutic Group Therapy and Family Psychoeducation